2011
DOI: 10.1542/peds.2010-3438
|View full text |Cite
|
Sign up to set email alerts
|

Pain Reduction on Insertion of a Feeding Tube in Preterm Infants: A Randomized Controlled Trial

Abstract: Insertion of a feeding tube in preterm infants leads to a measurable degree of pain and discomfort, according to the Premature Infant Pain Profile assessment tool. Pain relief was best achieved by combining a pacifier with 30% sucrose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…75,76 A recent meta-analysis revealed that glucose is an acceptable alternative to sucrose, decreasing PIPP scores and crying times associated with venipuncture and heel lance. 77 Sucrose is efficacious in reducing the pain from single events such as retinopathy of prematurity screening 78 , oral gastric tube insertion 79 and heel lance. 72 However, sucrose is controversial when given repeatedly, possibly leading to adverse long term outcomes.…”
Section: Non-pharmacologic Approachesmentioning
confidence: 99%
“…75,76 A recent meta-analysis revealed that glucose is an acceptable alternative to sucrose, decreasing PIPP scores and crying times associated with venipuncture and heel lance. 77 Sucrose is efficacious in reducing the pain from single events such as retinopathy of prematurity screening 78 , oral gastric tube insertion 79 and heel lance. 72 However, sucrose is controversial when given repeatedly, possibly leading to adverse long term outcomes.…”
Section: Non-pharmacologic Approachesmentioning
confidence: 99%
“…Considering that renewing a NG-tube causes measurable distress in preterm infants (10), we wanted to determine if NG-tubes yielded less bacteria to the infant, the shorter they had been in use. Furthermore, since the use of probiotics for preterm infants to prevent NEC and sepsis is gaining ground (11), and since Lactobacillus spp.…”
mentioning
confidence: 99%
“…In relation to nasogastric tube insertion, McCullough et al (2008) compared sucrose to a placebo in 20 stable preterm infants and found the former demonstrated lower facial pain scores. Similarly, Kristofferson et al (2011) also studied preterm neonates but compared pacifier use verses no pacifier combined with 30% sucrose, sterile water or nothing. The lowest pain scores were achieved by combining a pacifier with sucrose for nasogastric tube insertion.…”
Section: Discussionmentioning
confidence: 99%